The practice of transformational leadership and its role in achieving leadership excellence: A Case study of Al-Istiqlal University - Allaoua, Selma; Shaqour, Sari; Amari, Salah Eddine Sofiane (International journal of economic perspectives, 2024)
This study focuses on the concept of transformational leadership within the context of higher education institutions, particularly at Palestine University. The research emphasizes the distinction between transformational and transactional leadership, noting that transformational leaders inspire and motivate their followers to transcend their interests for the organizations benefit, while transactional leaders focus on reward-based exchanges. This contrast illustrates the broader impact transformational leadership has on organizational adaptability and effectiveness, particularly in changing environments. The study utilizes a mixed-methods approach, with data collected via questionnaires distributed among university staff. It employs structural equation modelling to analyse the relationships between the dimensions of transformational leadership and leadership excellence. Key results indicate that idealized influence has a strong positive effect on leadership excellence, while inspirational motivation also significantly improves leadership outcomes albeit to a lesser extent. Individual consideration and mental stimulation show statistically insignificant impacts. The study confirmed hypotheses suggesting a meaningful correlation between transformational leadership behaviours and perceived leadership success, particularly in promoting innovative practices and enhancing institutional performance.